Enhancing the performance and stability of perovskite solar cells using liquid crystal additive - Alishah, Hamed Moeini; Kahveci, Cihangir; Cakir, Irem; Kavak, Pelin; Gebremichael, Zekarias Teklu; Bhandari, Bashudev; Skriver, Pinar; Eran, Belkiz Bilgin; Gunes, Serap; Schubert, Ulrich S.; Hoppe, Harald; Canli, Nimet Yilmaz (ELSEVIER, 2025)
Perovskite solar cells (PSCs) have attracted considerable interest due to their outstanding power conversion efficiencies and potential for low-cost fabrication. To further enhance device performance and long-term stability, strategies such as additive engineering have gained momentum. The present study investigates the effects of incorporating 4-((S)-3,7-dimethyloctyloxy)-2-[[[4-(S)-2-methylbutoxyphenyl]imino]methyl]phenol (LC1) into the anti-solvent during perovskite film formation. Devices fabricated with varying concentrations of LC1 were systematically analyzed. The results show that the addition of LC1 at low concentration leads to improved film morphology, improved crystallinity and suppressed non-radiative recombination, as confirmed by FESEM, XRD and photoluminescence (PL) analyses, respectively. Furthermore, long-term stability tests over 20 days show that devices with low LC1 concentration maintain high power conversion efficiency with minimal degradation, outperforming both the reference and higher LC1 concentrations. These findings highlight the multifunctional role of LC1 in simultaneously improving performance and stability, establishing liquid crystal additives as promising candidates for next-generation, durable PSCs.
Keywords: Perovskite solar cells; Liquid crystal additives; Device stability; Anti-solvent processing; HALIDE PEROVSKITES; EFFICIENCY; Materials Science